Physiological responses of Saccharomyces cerevisiae to industrially relevant conditions: Slow growth, low pH, and high CO(2) levels - Hakkaart, Xavier (Biotechnol Bioeng, 2020)
Engineered strains of Saccharomyces cerevisiae are used for industrial production of succinic acid. Optimal process conditions for dicarboxylic‐acid yield and recovery include slow growth, low pH, and high CO(2). To quantify and understand how these process parameters affect yeast physiology, this study investigates individual and combined impacts of low pH (3.0) and high CO(2) (50%) on slow‐growing chemostat and retentostat cultures of the reference strain S. cerevisiae CEN.PK113‐7D. Combined exposure to low pH and high CO(2) led to increased maintenance‐energy requirements and death rates in aerobic, glucose‐limited cultures. Further experiments showed that these effects were predominantly caused by low pH. Growth under ammonium‐limited, energy‐excess conditions did not aggravate or ameliorate these adverse impacts. Despite the absence of a synergistic effect of low pH and high CO(2) on physiology, high CO(2) strongly affected genome‐wide transcriptional responses to low pH. Interference of high CO(2) with low‐pH signaling is consistent with low‐pH and high‐CO(2) signals being relayed via common (MAPK) signaling pathways, notably the cell wall integrity, high‐osmolarity glycerol, and calcineurin pathways. This study highlights the need to further increase robustness of cell factories to low pH for carboxylic‐acid production, even in organisms that are already applied at industrial scale.